2021
DOI: 10.21203/rs.3.rs-124394/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corona children studies "Co-Ki": First results of a Germany-wide registry on mouth and nose covering (mask) in children

Abstract: Background: Narratives about complaints in children and adolescents caused by wearing a mask are accumulating. There is, to date, no registry for side effects of masks.Methods: At the University of Witten/Herdecke an online registry has been set up where parents, doctors, pedagogues and others can enter their observations. On 20.10.2020, 363 doctors were asked to make entries and to make parents and teachers aware of the registry.Results: By 26.10.2020 the registry had been used by 20,353 people. In this publi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…54 Continuous mask-wearing may be especially dangerous for children as they block the normal oxygen flow which may have serious consequences for brain injuries or brain development of children and adolescents. A recent German study, even if preliminary, 55 found health consequences in 68% of masked children that were forced to wear a face covering for an average of 4.5 hours per day. The study comprised 17,854 health complaints that were submitted by parents as well.…”
Section: Recombinant Genetic Products Used For Covid-19 Vaccinationmentioning
confidence: 99%
“…54 Continuous mask-wearing may be especially dangerous for children as they block the normal oxygen flow which may have serious consequences for brain injuries or brain development of children and adolescents. A recent German study, even if preliminary, 55 found health consequences in 68% of masked children that were forced to wear a face covering for an average of 4.5 hours per day. The study comprised 17,854 health complaints that were submitted by parents as well.…”
Section: Recombinant Genetic Products Used For Covid-19 Vaccinationmentioning
confidence: 99%